All aboard?! Co-viewing with and within connected platforms in the Eurovision Song Contest - Pires,Fernanda (2020)
Abstract Based on co-viewing and connected viewing literature (Pires & Roig, 2016), this article analyses connected co-viewing practices within and with the use of media platforms around a live television event, using the Eurovision Song Contest as a case study. This popular event has a long-running tradition which has fostered extensive use of different kinds of connected platforms, including an official app. Using a case study approach and focusing on the Spanish context, we have analysed connected co-viewing in three main platforms: Facebook (through unofficial groups), Twitter (through live conversation and hashtagging practices around the event) and by exploring the Eurovision official second screen app. The study indicates that: (1) co-viewing is mutually shaped by the affordances and interface features of the platforms, the viewers’ practices and uses given to these platforms; (2) co-viewing can be expanded by platforms when designed for collective use; (3) user-generated content and data production are central elements to enhance co-viewing when using connected platforms; (4) platform affordances can create digital spaces, which might channel the way co-viewers perform and enjoy this activity.